Spatial heterogeneity of the hepatocellular carcinoma microenvironment determines the efficacy of immunotherapy - Minni Zhang; Kailin Huang; Qiushi Yin; Xueqin Wu; Mingyue Zhu; Mengsen Li (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC) remains a global health challenge owing to its widespread incidence and high mortality. HCC has a specific immune tolerance function because of its unique physiological structure, which limits the efficacy of chemotherapy, radiotherapy, and molecular targeting. In recent years, new immune approaches, including adoptive cell therapy, tumor vaccines, and oncolytic virus therapy, have shown great potential. As the efficacy of immunotherapy mainly depends on the spatial heterogeneity of the tumor immune microenvironment, it is necessary to elucidate the crosstalk between the composition of the liver cancer immune environment, from which potential therapeutic targets can be selected to provide more appropriate individualized treatment programs. The role of spatial heterogeneity of immune cells in the microenvironment of HCC in the progression and influence of immunotherapy on improving the treatment and prognosis of HCC were comprehensively analyzed, providing new inspiration for the subsequent clinical treatment of liver cancer.